Prediction from chemical analyses of energy value and nitrogen digestibility of feed ingredients and diets for swine - Hsu, Ali; Allee, G.L.; Pollmann, D.S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Nine individual feed ingredients and 12 mixed diets were used in an attempt to select the most suitable regression equation for predicting energy value and nitrogen digestibility from chemical analyses. Samples were analyzed for crude protein (CP), ether extract (EE), crude fiber (CF), ash, moisture and nitrogen-free extract (NFE). Feed ingredients were corn, sorghum grain, wheat (trial 1), alfalfa meal, wheat bran, rice bran (trial 2), soybean meal, meat and bone meal and sunflower meal (trial 3). Levels ranged from 9.9 to 53.9% for CP, from 1.5 to 25.5% for CF, and from 1.7 to 27.3% for ash. A total of 72 pigs with average initial weight of 25 kg (55 lb) were used in three conventional digestion trials to measure the dry matter digestibility (DMD), nitrogen digestibility (ND), digestible energy (DE) and metabolizable energy (ME) of diets and feed ingredients. Feed ingredients were substituted for the basal diets at 50, 30 and 20% in trial 1, 2 and 3, respectively. The DMD, ND, DE and ME were measured by difference between determined values for the test ingredient and the basal diet. Fiber was the major factor depressing DMD, ND, DE and ME in both diets and feed ingredients. Levels of crude fiber and protein affected the ratio of ME to DE in feed ingredients as in the following equation: ME/DE, % = 100.4 - .12 CP - .15 CF (r = .94, P<.01). High correlations were found between ME and DE and DMD in diets and feed ingredients. The DE and ME in feed ingredients could be predicated from only CF and ash by the following equations: DE, kcal/ g DM = 4.360 - .0652 CF - .0489 ash (r = .93, P<.0l); and ME, kcal/g DM = 4.277 - .0676 CF - .0516 ash (r = .95, P<.00l). These results suggest that nitrogen digestibility and digestible energy of feed ingredients and complete diets for swine can be estimated from chemical analyses.
Keywords: Swine; Energy value; Nitrogen digestibility; Ingredients